Advances in Informatics and Computing in Civil and Construction Engineering Proceedings of the 35th CIB W78 2018 Conference: IT in Design, Construction, and Management - Mutis, Ivan; Hartmann, Timo (Springer International Publishing : Imprint: Springer, 2019)
This proceedings volume chronicles the papers presented at the 35th CIB W78 2018 Conference: IT in Design, Construction, and Management, held in Chicago, IL, USA, in October 2018. The theme of the conference focused on fostering, encouraging, and promoting research and development in the application of integrated information technology (IT) throughout the life-cycle of the design, construction, and occupancy of buildings and related facilities. The CIB - International Council for Research and Innovation in Building Construction - was established in 1953 as an association whose objectives were to stimulate and facilitate international cooperation and information exchange between governmental research institutes in the building and construction sector, with an emphasis on those institutes engaged in technical fields of research. The conference brought together more than 200 scholars from 40 countries, who presented the innovative concepts and methods featured in this collection of papers. Some of the papers' topics included the following: • Virtual, augmented, and mixed reality • Visualization and simulation • Communication and collaboration informatics • Sensor data interpretation • Situation awareness and sensing technologies • Mobile computing • Geometric and parametric modeling • Building information modeling (BIM) • 4-D/n-D modeling • Computer-enhanced engineering design • Design and decision support systems • Ontologies and reasoning for civil and construction engineering • Semantic modeling in the AEC industry • Product and process modeling • Data acquisition, analysis, and storage.